Impact of interproximal composite restorations on periodontal tissue health: Clinical and cytokine profiles from a pre‐post quasi‐experimental study. Issue 6 (12th October 2021) - Discepoli, Nicola; Marruganti, Crystal; Santoro, Francesco; Mirra, Raffaele; Fiorino, Fabio; Medaglini, Donata; Pozzi, Gianni; Ferrari, Marco; Grandini, Simone
Abstract: Background: The aim of this study is to clinically and molecularly evaluate the effect of an interproximal iuxta/subgingival direct composite restoration on periodontal tissue healing. Methods: Individuals in need of a posterior iuxta/subgingival interproximal restoration were consecutively enrolled. After enrollment, a test (site with tooth decay) and a control site (intact contralateral tooth) were identified. After a periodontal examination (probing depth [PD], clinical attachment level, recession, plaque, and bleeding on probing [BOP]) and a sampling of gingival crevicular fluid, the composite restoration was performed (T0 ). Clinical and molecular assessments were repeated at 3 (T3 ), 6 (T6 ), and 12 (T12 ) months after the restoration. Intragroup pre‐post comparisons for quantitative variables were performed either through one‐way ANOVA or Kruskal‒Wallis test. A multivariate linear regression analysis was then modeled. With α = 0.05, a power of 80% will be reached with the inclusion of 41 individuals. Results: Biometric parameters demonstrated an increased mean PD (ΔPDT0 ‐T12 = ‐0.83 mm; P = 0.001) and loss of attachment (AL) (ΔCALT0 ‐T12 = ‐0.91 mm; P = 0.005) in the test site at 12 months. Accordingly, in the final multivariate regression model the radiographic distance between the bone crest and the restorative margin at baseline accounted for the dependent variable "attachment loss (AL)" (ΔCALT0 ‐T12 ) ( P <0.05). Conclusions: Iuxta/subgingival interproximal restorative margins jeopardized clinically and molecularly the periodontal tissue healing at least up to 1 year of follow‐up.